2020
DOI: 10.1371/journal.pone.0228954
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to white blood cell elevation in acute type A aortic dissection

Abstract: Aortic dissection may induce a systemic inflammatory reaction. The etiological backgrounds for elevation of the white blood cell count remain to be clarified. In 466 patients with acute type A aortic dissection treated surgically within 48 hours of symptom onset, the etiologic background of an elevated admission white blood cell count and the effect of such elevation on outcomes were assessed retrospectively. Patients' white blood cell count differed significantly in relation to the extent of dissection, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…The initial assessment and diagnosis of AD by routine examination is not easy at present, the misdiagnosis rate is high, and routine laboratory tests have no specific significance for the diagnosis of aortic coarctation and can only be used to exclude other diagnostic possibilities [ 37 ]. Occasionally, the acute onset of aortic coarctation may be associated with stress-related leukocytosis or anemia due to severe bleeding and massive blood flow into the false lumen, with individual diffuse intravascular coagulation [ 38 ]. Serum aminotransferases are generally not elevated unless myocardial infarction occurs with involvement of the coronary artery by a clotted hematoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial assessment and diagnosis of AD by routine examination is not easy at present, the misdiagnosis rate is high, and routine laboratory tests have no specific significance for the diagnosis of aortic coarctation and can only be used to exclude other diagnostic possibilities [ 37 ]. Occasionally, the acute onset of aortic coarctation may be associated with stress-related leukocytosis or anemia due to severe bleeding and massive blood flow into the false lumen, with individual diffuse intravascular coagulation [ 38 ]. Serum aminotransferases are generally not elevated unless myocardial infarction occurs with involvement of the coronary artery by a clotted hematoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated white blood cell count has been observed in patients with aortic dissection in previous studies and was associated with adverse events [5,8]. The elevation of the white blood cell count may associate with the acute phase systemic in ammatory response [14].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have indicated that the in ammatory response may play a critical role in AD initiation and progression [8,[11][12][13][14]. However, previous research mainly focused on the role of neutrophil counts in AD prognosis [8, [15][16][17] but not in AD diagnosis.…”
Section: Discussionmentioning
confidence: 99%